Decision Support System for Recommendation Sharia Banking Investment Products Using Simple Additive Weighting (SAW) - Muhammad Ivan Mukti; Winny Purbaratri; Pratiwi; Lucia Sri Istiyowati; Zahwa Bunga Ranien (Komunitas Dosen Indonesia, 2024)
The swift expansion of Islamic banking has resulted in the creation of many investment products, such as mudharabah deposits, sukuk, and Islamic mutual funds, all compliant with sharia rules. Notwithstanding this advancement, the customers' inadequate financial literacy presents considerable obstacles in identifying appropriate investment alternatives that correspond with their objectives and risk appetite. This work seeks to fill this gap by creating a Decision Support System (DSS) that employs the Simple Additive Weighting (SAW) method to aid users in making educated decisions on Islamic banking investments. The SAW technique was selected for its straightforwardness and efficacy in normalizing data and assessing alternatives according to established criteria, including profit potential, risk level, investment duration, and compliance with sharia principles. The research encompassed multiple phases, including the identification of evaluation criteria, the collection and analysis of pertinent data, and the application of the SAW method to rank investment choices. The DSS effectively delivered precise and dependable suggestions, designating Sharia Deposits as the optimal investment choice due to its robust agreement with the established criteria. The results underscore the system's capability to improve financial inclusion and literacy, especially in Indonesia, where comprehension of sharia-compliant financial products is still inadequate. Future improvements to the DSS involve the incorporation of real-time data and the expansion of its application to include more financial industries, such as insurance and microfinance. This study highlights the importance of utilizing technology to address deficiencies in financial literacy and facilitate the sustainable development of the Islamic banking sector.